The Effect of Various Decomposers on Quality of Cattle Dung Compost - Nur Shoodiq Alfadlli; Safuan Noor; Bayu Setya Hertanto; Muhammad Cahyadi (Buletin Peternakan, 2018)
The aim of this study was to compare the utilization of decomposer from bioethanol waste (DLB) with various commercial decomposers on quality of compost made from cattle dung. This study used completely randomized design (one-way ANOVA) with four treatments and five replications. Materials used in this study were cattle dung, water, molasses, DLB and various commercial decomposers (A, B, and C). The treatments in this study were cattle dung + BLB 0.5% (P0), cattle dung + decomposer A 0.5% (P1), cattle dung + decomposer B 0.5% (P2) and cattle dung + decomposer C 0.5% (P3). Then, the mixtures were aerobically ripened until four weeks. During composting, compost was stirred weekly. Furthermore, mature compost was analyzed to evaluate the amount of C Organic, total N, total P, total K, total Ca, total Mg, C/N ratio and pH value. The analysis of variance showed that there was no difference of the quality and pH value of compost made from cattle dung with utilization of DLB and commercial decomposers. It could be concluded that utilization of DLB in composting of cattle dung had identically quality and pH value of compost with utilization of commercial decomposers, therefore, this technology could be an alternative to process waste from home industry of bioethanol.